Therapeutic equivalence of vildagliptin 100 mg once daily modified release to 50 mg twice daily immediate release formulation: An open-label, randomized, two-period, single- and multiple-dose, 6-day crossover study. Issue 3 (March 2022) - Sangana, Ramachandra; Mittal, Hemant; Barsainya, Sarita; Hoermann, Aldo; Borde, Parag; Naik, Sachin; Thorat, Anup Vilas; Zhang, Jie; Valentin, Marie-Anne; Kalluri, Sampath
Abstract: Background and aims: Vildagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor to treat type 2 diabetes mellitus, is available as immediate release (IR) tablets administered at 50 mg twice daily (BID). A 100 mg modified release (MR) formulation was developed for once daily (QD) dosing. This study aimed to compare the therapeutic equivalence of vildagliptin 100 mg MR QD (test) and 50 mg IR BID (reference) formulations at steady state under fasting conditions. Methods: This was an open-label, randomized, two-period, single- and multiple-dose, two-way crossover, steady state study conducted in healthy adult subjects. Both vildagliptin formulations were administered for six days. Endpoints included pharmacodynamic equivalence, pharmacokinetic parameters, and tolerability of both formulations. Results: Thirty subjects were enrolled and 26 completed both treatments. Maximum plasma concentration and exposure achieved with test was lower than reference formulation on day 1 and 6. The DPP-4 enzyme inhibition over time (DPP-4-AUEC0-24 ) was comparable between the formulations. Both formulations were well tolerated. Conclusion: This study confirms the therapeutic equivalence of vildagliptin IR and MR formulations for DPP-4 enzyme inhibition over time. The study supports vildagliptin 100 mg MR QD as a useful therapeutic alternative to 50 mg IR BID formulation to possibly improve treatment adherence and patient compliance. Long-term safety of the vildagliptin 100 mg MR QD formulation is not evaluated in this study. Highlights: To address patients' treatment adherence needs, vildagliptin 100 mg once daily modified release formulation was developed. Study confirms therapeutic equivalence (DPP4 enzyme inhibition over time) between IR and MR formulations of vildagliptin. Vildagliptin 100 mg MR once daily formulation can be used as therapeutic alternative to 50 mg IR twice daily tablet in India.